Patent Law in Biotechnology, Chemicals & Pharmaceuticals - Wegner, Harold C. author. aut Link
XX, 514 p.
Keywords: A practical guide to patent prosecution and strategy in the US with particular reference to invention in chemicals and biotechnology. The presentation is focused on case law in the US and deals with specific cases. A section is devoted to international patent protection.